Frequency and Temperature Dependence of Fabrication Parameters in Polymer Dispersed Liquid Crystal Devices - Torres, Juan C. (Materials (Basel), 2014)
A series of polymer dispersed liquid crystal devices using glass substrates have been fabricated and investigated focusing on their electrical properties. The devices have been studied in terms of impedance as a function of frequency. An electric equivalent circuit has been proposed, including the influence of the temperature on the elements into it. In addition, a relevant effect of temperature on electrical measurements has been observed.